Job Attribute Preferences of Generation Y Professionals - Yasmin, Shakila; Mahmud, Khaled; Afrin, Farzana (Selected Topics in Humanities and Social Sciences Vol. 2, 2021)
This research explores the job attribute preferences of the Generation Y professionals in Bangladesh. Unlike most past researches that deployed isolated estimation methods, this research used conjoint analysis, a marketing research tool to measures the relative utilities and trade-off matrices of different job attributes. Data was collected from 140 executive MBA students from a premier business school in Dhaka using a questionnaire presenting an array of hypothetical job offers (HJO). Salary & benefit and person-job match are found to be the top two most preferred job attributes. Work environment and company- reputation are indicated as the two least important job attributes. Simulation was run to demonstrate the trade-offs people make in their job choice decisions. Case-wise conjoint results show no significant difference among different demographic groups (e.g. married-single, have-don’t have dependents and others) in terms of the order of importance of the job attributes. However, the value of the relative importance was found to be slightly different for different demographic groups. This research is important for academics as it demonstrate a new technique to analyze job attribute preferences. Managers can use the results of this study for designing jobs to attract and retain the best talents of the market. They can use the simulation process demonstrated here for optimizing overall preference of their job offers.